The unforeseen intracellular lifestyle of Enterococcus faecalis in hepatocytes - Natalia Nunez; Aurélie Derré-Bobillot; Nicolas Trainel; Goran Lakisic; Alexandre Lecomte; Françoise Mercier-Nomé; Anne-Marie Cassard; Hélène Bierne; Pascale Serror; Cristel Archambaud (Gut Microbes)
Enterococcus faecalis is a bacterial species present at a subdominant level in the human gut microbiota. This commensal turns into an opportunistic pathogen under specific conditions involving dysbiosis and host immune deficiency. E. faecalis is one of the rare pathobionts identified to date as contributing to liver damage in alcoholic liver disease. We have previously observed that E. faecalis is internalized in hepatocytes. Here, the survival and fate of E. faecalis was examined in hepatocytes, the main epithelial cell type in the liver. Although referred to as an extracellular pathogen, we demonstrate that E. faecalis is able to survive and divide in hepatocytes, and form intracellular clusters in two distinct hepatocyte cell lines, in primary mouse hepatocytes, as well as in vivo. This novel process extends to kidney cells. Unraveling the intracellular lifestyle of E. faecalis, our findings contribute to the understanding of pathobiont-driven diseases.